Pencegahan Perkawinan Oleh Wali Nasab Dalam Putusan Pengadilan Agama Selong Kelas 1 B - Badar, Muhammad Badaruddin; Teti Indrawati Purnamasari; Zainal Arifin Haji Munir (Fakultas Syariah Institut Agama Islam Negeri Palu, 2023)
Marriage laws in Indonesia for the Muslim community are regulated in the Compilation of Islamic Law (HKI). It does not rule out the possibility that disputes may arise during the marriage process. Two people who love each other and want to carry out the orders of Allah and His Messenger, also want to realize article 3 in the Compilation of Islamic Law, are prevented by their own lineage guardian because they do not agree with their child's marriage. This conflict occurred because there was a gap in legal remedies for family guardians who did not agree with their child's marriage, as well as legal remedies for women whose guardians were reluctant to become guardians for their marriage. This article is field research using qualitative research methods that are descriptive analysis. The approach used in this research is a case approach. The object of study in this article is the decision of the Selong Religion regarding the prevention of marriage by lineage guardians. The prevention of marriage carried out by the nasab guardian in the decision of the Selong Religious Court was due to the fact that the nasab guardian did not want his child to be used as a second wife or polygamous, in the process of escape or extramarital affairs carried out by the groom which was not in accordance with the customs applicable in the bride's area, and between the bride and groom. men and women are not equal. These three cases were not a valid reason for the nasab guardian to prevent the marriage of his child from the perspective of the Compilation of Islamic Law (KHI), so the request was rejected by the panel of judges.